2011
DOI: 10.1534/g3.111.000752
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Diversity of Chloroplast Noncoding RNAs as Revealed by Deep Sequencing of the Arabidopsis Transcriptome

Abstract: Noncoding RNAs (ncRNA) are widely expressed in both prokaryotes and eukaryotes. Eukaryotic ncRNAs are commonly micro- and small-interfering RNAs (18–25 nt) involved in posttranscriptional gene silencing, whereas prokaryotic ncRNAs vary in size and are involved in various aspects of gene regulation. Given the prokaryotic origin of organelles, the presence of ncRNAs might be expected; however, the full spectrum of organellar ncRNAs has not been determined systematically. Here, strand-specific RNA-Seq analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 57 publications
3
93
0
1
Order By: Relevance
“…More than 10 7 reads were obtained from each sample, of which ;75% aligned to the chloroplast genome (Supplemental Table 1), an increase over the 30 to 50% of chloroplast-specific reads obtained from total leaf RNA (Hotto et al, 2011). Reads per kilobase of transcript per million mapped reads (RPKM) values for exons and introns showed that expression levels between replicates were highly reproducible (Supplemental Figure 7; r $ 0.93).…”
Section: Rna-seq Validates a Role For Mini-iii In Rrna Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 7 reads were obtained from each sample, of which ;75% aligned to the chloroplast genome (Supplemental Table 1), an increase over the 30 to 50% of chloroplast-specific reads obtained from total leaf RNA (Hotto et al, 2011). Reads per kilobase of transcript per million mapped reads (RPKM) values for exons and introns showed that expression levels between replicates were highly reproducible (Supplemental Figure 7; r $ 0.93).…”
Section: Rna-seq Validates a Role For Mini-iii In Rrna Maturationmentioning
confidence: 99%
“…These enzymes and factors include a variety of RNases (Stoppel and Meurer, 2012) and large families of sequencespecific RNA binding proteins, such as those of the pentatricopeptide repeat (PPR) and RNA recognition motif families (Ruwe et al, 2011;Nakamura et al, 2012). Evidence from high-throughput RNA sequencing (RNA-Seq) and microarrays suggests that both strands of the ;150-kb chloroplast genome are fully transcribed (Hotto et al, 2011;Zmie nko et al, 2011;Zhelyazkova et al, 2012), emphasizing the critical role of posttranscriptional processes in defining the steady state RNA population.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RNAs antisense to ycf1 were detected in a deep-sequencing study of the Arabidopsis chloroplast transcriptome and in mutants of the chloroplast PNPase, which is a 39-to-59 exonuclease (Hotto et al, 2011). RNA gel blot analyses demonstrated that this PNPase is needed for the accumulation of processed as-ycf1 transcripts (Hotto et al, 2011). In the future, studies on the interplay among CP31A, PNPase, and other factors will allow us to understand how chloroplast 39-degradation of ndhF (and potentially other mRNAs) is regulated.…”
Section: Cp31a Stabilizes the Ndhf Mrna By Protecting Its 39-endmentioning
confidence: 99%
“…However, the functions of other classes of potential RNA regulators, such as long noncoding RNAs and cis-natural antisense transcripts, are scarcely understood (De Lucia and Dean, 2011). Noncoding RNAs are not only transcribed in the plant nucleus but are also abundant in plant chloroplasts (Hotto et al, 2011;Zhelyazkova et al, 2012). With regard to the possible involvement of noncoding RNAs in plastidrelated regulatory networks, it is unclear at present whether these have evolved from their cyanobacterial ancestors and to what extent such regulators play a role in cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%